A Multi-Stage Batch Sorption Design with Experimental Data - Y.S. Ho; G. McKay (Adsorption Science & Technology)
The sorption of lead ions on to peat in an agitated batch adsorber has been studied. A model has been developed for the design of a two-stage batch adsorber based on pseudo second-order sorption kinetics. The model has been optimised with respect to contact time in order to minimise total contact time to achieve a fixed percentage of metal ion removal.